(untitled) (Entrepreneurship Journal for Finance and Business, 2026)
This research aims to explore the role of accounting in improving the financial performance of both public and private institutions, focusing on how modern accounting tools such as Enterprise Resource Planning (ERP) systems and cloud-based accounting software can enhance financial efficiency and increase transparency. The study adopts a descriptive-analytical approach, using surveys to collect data from accountants and financial managers within various institutions. Financial performance was assessed using key financial indicators such as Return on Investment (ROI), Return on Assets (ROA), liquidity ratios, and profitability ratios. Additionally, the research analyzes the economic and regulatory challenges institutions face in implementing modern accounting systems and the impact these challenges have on the accuracy of financial reporting. The findings indicate that the use of modern accounting systems significantly improves financial efficiency by accelerating the process of data collection and analysis, thus enabling more accurate strategic decision-making. The results also reveal that institutions face economic and regulatory challenges, such as changes in laws and regulations, which affect the effectiveness of accounting systems. The research concludes that adopting modern accounting systems positively impacts financial performance but requires a flexible environment to adapt to economic and regulatory challenges.